Kredibilitas Joko Widodo Dalam Vlog #JKWVlog di Generasi Milenial Kota Denpasar - Arie Rahayu, Ni Komang Mirah; Pradipta, Ade Devia; Purnawan, Ni Luh Ramaswati (E-Jurnal Medium, 2020)
President Joko Widodo is a political communicator who uses vlog content to communicate with the millennial generation. As a source or communicator in the digital era, having good credibility in building effective communication through the media is very important. The purpose of this study is to find out Joko Widodo's credibility in the #JKWVlog Vlog  in the Millennial Generation of Denpasar City. This research uses the descriptive quantitative method and was analysied with the theory of Source Credibility by Hovland, Janis, and Kelley (1953). The results showed that Joko Widodo's credibility as seen in the #JKWVlog vlog was categorized good because the millennial generation had a good assessment of expertise and attractiveness, as well as high trust in Joko Widodo as a political communicator. Keywords: President Joko Widodo, Vlog, Credibility, Millennial Generation.